(untitled) (Revista de Estudos da Linguagem, 2003)
Heidegger, in his most radical work, “Unterwegs zur Sprache”,pointed out the role of the unnamable in the poetic performanceas possibilibity of experiencing speech. In this sense, it would bein the lack of words that the dimension of the word as restorer ofbeing and the world becomes more evident. This article aims todiscuss how the experience of the unnamable, present as existentialpain in Marguerite Duras’s writings, opens up the possibility offorming a fertile soil for the occurrence of that experience.